Automotive graphic sticker design: variation, interaction and perception / Norazmi Shahlal - Shahlal, Norazmi (2018)
This research explored the impact of car design sticker application to the external body surface. Frequently the manufacturer or consumer used sticker to beautify, differentiate and means of communication. The design of the cars has been viewed for its function either as a sedan, hatchback, station wagon or others. Within the model produced, manufacturer tend to diversify the target audience of the similar model by having different painting treatment, little changes on bumper, grille or the skirting. These have been done to demonstrate the appearance of sporty, elegance, rugged, feminine or even the norm plain model. The cost, timeframe, machine, expertise and consumer perception unnecessarily will deliver positivism impact value to the new car design. It is believe that the Car Graphic Sticker Design (CGSD) factor reflects new value design perception in the design process by creating new appearance to the external body surface. The investigations seek for the possibilities on how CGSD able to differentiate the similar model range to meet the specific consumer and possibilities of a potential alternative material application for manufacturers instead of painting or body changes (bumper, skirting, grille and others). The mixed method of qualitative and quantitative employed in this research were used to get information to assess CGSD as potential alternative material application for five purposive main automotive manufacture in Malaysia. The 26 structured survey in Likert Scale, with 158 fractioned questionnaires and car model in production with CGSD in visual observation. 32 cars divided in mini, sedan, sport, luxuries and sport utility vehicle as standard production segmentation models indicated design theme from CGSD design experiment with semantic visualization by the clustering approach were explored in specific graphic sticker design in selected production. The purposive participation from automotive designers, managerial in manufacturers and consumer been interviewed based from 11 content themes and questionnaires. The survey examined the graphic applied on external car body surface demonstrated 94.7% as a design factor of the car differentiation in mass production. The application as body paint replacement indicated 79.6% and 67.2% as factor of the reduce environment issue. Interview method clustered, manufacture and consumer examined the content analysis through themes structured in design value, purpose of sticker, function, value and sticker as an alternative to the car design on body surface appearance. Nevertheless, interview demonstrated different content analysis value which Respondents 7, 8, 9, 10, 11 and 12 explained the vital and precise to the sticker as model differentiate from body surface appearance and paint replacement. Respondents 1, 2 and 3 explained principle value content on existence of the graphic. While, Respondents 4, 5 and 6 examined inconsistence descriptive valued to the sticker. The data provided a rigorous input and findings contribute to the knowledge in method of external car body surface changes process. These enable to differentiate appearance for a target consumer with maintaining the brand image and identity as holistic design point of reference for automotive design practice, design education and policies maker that reflects to the design environment concern in automotive manufacturer.